Host Shift Speciation of the Ectomycorrhizal Genus Suillus (Suillineae, Boletales) and Biogeographic Comparison With Its Host Pinaceae - Zhang, Rui; Shi, Xiao-fei; Liu, Pei-gui; Wilson, Andrew W.; Mueller, Gregory M. (Frontiers in Microbiology, 2022)
Suillus is a genus of ectomycorrhizal fungi associated almost exclusively with Pinaceae. Lack of sample collections in East Asia and unresolved basal phylogenetic relationships of the genus are the major obstacles for better understanding the Suillus evolution. A resolved phylogeny of Suillus representing global diversity was achieved by sequencing multiple nuclear ribosomal and protein coding genes and extensive samples collected in East Asia. Fungal fossils are extremely rare, and the Eocene ectomycorrhizal symbiosis (ECM) fossil of Pinus root has been widely used for calibration. This study explored an alternative calibration scenario of the ECM fossil for controversy. Ancestral host associations of Suillus were estimated by maximum likelihood and Bayesian MCMC analyses, inferred from current host information from root tips and field observation. Host shift speciation explains the diversification of Suillus major clades. The three basal subgenera of Suillus were inferred to be associated with Larix, and diverged in early Eocene or Upper Cretaceous. In the early Oligocene or Paleocene, subgenus Suillus diverged and switched host to Pinus subgenus Strobus, and then switched to subgenus Pinus four times. Suillus subgenus Douglasii switched host from Larix to Pseudotsuga in Oligocene or Eocene. Increased species diversity occurred in subgenus Suillus after it switched host to Pinus but no associated speciation rate shifts were detected. Ancestral biogeographic distributions of Suillus and Pinaceae were estimated under the Dispersal Extinction Cladogenesis (DEC) model. Ancestral distribution patterns of Suillus and Pinaceae are related but generally discordant. Dispersals between Eurasia and North America explain the prevalence of disjunct Suillus taxa.